Efforts to optimize thinking skills and acting through kit media in science learning in class vi sd 31 ambacang Kecamatan bayang - Surya Ningsih (Jurnal Ilmiah Pendidikan Scholastic, 2018)
This research is based on the problems that arise in science learning, especially on basic matter or competence "Understanding the influence of human activities on environmental balance" in Grade VI of First Semester State Elementary School 31 Ambacang Bayang District. Teachers in various ways have made it possible for all students to be active in learning activities. Standardized learning has also been implemented, the various learning media that exist in schools have been utilized. Nevertheless, in a variety of question and answer opportunities, class discussions, as well as daily tests, their activities and learning achievements are very low. Based on teacher record, student achievement in question and answer and class discussion are only 30% and 35% from 22 students respectively. Most of the students show irrelevant achievements in learning, such as being dazed and daydreaming, lack of excitement, lack of attention, playing alone, talking to friends when described, talking awkwardly or dialogue with friends during discussions, and so on. From the various possible factors, the teacher is more inclined to the 4th factor, the difficulty factor of adaptation and cooperation among the students, and it is strongly suspected as the main factor causing the low achievement of the students of Grade VI of Semester I SD Negeri 31 Ambacang Bayang District on the eyes Science lessons, especially on Basic materials / competencies: "Understand the impact of human activities on environmental balance". The approach in terms of the learning method chosen and used in this action research is "Media KIT IPA". Based on the background of thought that has been unraveled then this class action research is formulated with the title as follows: "Efforts to Optimize Thinking Skills And Acting Through KIT Media In Science Learning In Grade VI Elementary School 31 Ambacang District Bayang." In the end, it is hoped that through Media KIT IPA it can trigger and spur the spirit of togetherness, mutual help and mutual motivation among students, which in turn can also improve their learning achievement and achievement in the field of science study.